Addressing Climate Change: What Can Plant Invasion Science and Weed Science Learn From Each Other? - Sun, Yan; Kaleibar, Behnaz Pourmorad; Oveisi, Mostafa; Müller-Schärer, Heinz (Frontiers in Agronomy, 2021)
Plant invasion science and weed science, both dealing with harmful plants, have historically developed in separation. This may also be true for how the two fields are addressing the consequences of future climate change. Here, we first conducted a literature survey to explore how researchers in these two disciplines study the effects of climate change, and then identified their characteristic approaches to determine what the disciplines can learn from each other to better understand, predict and mitigate the outcomes of responses of harmful plants to climate change. Over the past 20 years, we found a much steeper increase in publications dealing with climate change for invasive alien plants (IAP) than for weeds. However, invasion scientists have to date only rarely investigated climate change effects at the local scale, such as on functional traits and population dynamics. In contrast, weed science could benefit from studies at larger scale, such as using a modelling approach to predict changes in weed distributions. Studies assessing the impacts of the target plants on ecosystem properties and on society, and on their management under climate change are important components of weed studies but remain neglected for IAP. This is despite an urgent need, especially because under climate change, abandoned cropland and areas of high conservation value are facing increasing risk from IAP. We argue that the strengths and diversity of approaches of these two disciplines in studying the effects of climate change are complementary and that closer ties between them would be highly beneficial for both.